HUBUNGAN ANTARA LAYANAN INFORMASI KARIR DENGAN PEMAHAMAN KARIR PESERTA DIDIK KELAS XI SMA - Vilkanova Mila; Yuline Yuline; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis research aims to find out more in depth about the relationship between career information services with the understanding of career learners. The method used is descriptive method with quantitative approach, namely problem-solving procedure by describing the relationship of career information service with career understanding by means of statistics and described descriptively. The sample of this study amounted to 57 students of class XI. Data collection techniques used are indirect communication techniques and documentary/bibliographic study techniques. The data collection tools used were questionnaires and student documents. Data analysis technique used to answer sub problem one and two is percentage, while to answer sub problem three using product moment correlation. The result of data analysis shows that career information service on class XI students reach 73,39%. The achievement is in the good range. Meanwhile, the understanding of career of class XI students reached 78.01% which is in the good range. The result of product moment correlation of both variables is obtained rhitung = 0.387 which means show that there is a positive correlation between career information service with understanding of career of class XI student of State Senior High School 4 Pontianak.Keywords: Career Information Service, Understanding of Career